The Good, the Beautiful, and the True Aesthetical Issues in Islamic Philosophy - Kukkonen, Taneli (Studia Orientalia Electronica, 2011)
“Islamic aesthetics” is something of a tricky designation when approached from a philosopher’s point of view, or for that matter a historian’s. Without a doubt, many of the Muslim philosophers wrote on topics which a modern student of aesthetics would find of interest. Abū Naṣr al-Fārābī’s (d. 950) forays into music are well known, for instance; Ibn Ṭufayl’s (d. 1185) less so, although we know that he, too, fancied himself a musicologist. The long-standing tradition of commenting on Aristotle’s Rhetoric and Poetics, meanwhile, meant that a sizeable body of work formed around the question of what constitutes pleasing, effective, and persuasive speech. Most pertinently for our present purposes, we have a series of rich philosophical discussions surrounding the use of the sense organs and the way in which pleasure figures in both sensory and intellectual cognition. These frequently incorporate at least some comments on the part of the Arabic philosophers regarding the aesthetic aspect of human experience, especially when it comes to the superior joys that occur when one comes face to face with the divine. I shall examine one such meditation in the principal part of this study.